Application of Scanning Towards Passing Accuracy in Football - Muhamad Ryan Nugraha; Yadi Sunaryadi; Widi Kusumah (Universitas Negeri Semarang, 2025)
This study investigated the effect of integrating scanning into a diamond passing training program on the passing accuracy of U13 football players at SSB Saswco FC Bandung. We used a quantitative quasi-experimental method with a one-group pretest–posttest design. Total sampling was used to choose all 20 eligible 13-year-old players. Prior to and following a four-week intervention (three sessions per week for sixty minutes each), passing performance was evaluated using the Loughborough Soccer Passing Test (LSPT). We used a paired-samples t-test, the Shapiro-Wilk normality test, and effect size computation to compare pretest and posttest results. The results showed that as LSPT scores decreased from the pretest (M = 64.10, SD = 5.04) to the posttest (M = 60.90, SD = 4.13), passing performance improved. The paired-samples t-test showed a significant improvement following the intervention (t(19) = 8.587, p < 0.001) with a very large effect (Cohen’s dz ≈ 1.92), and the normalcy assumptions were satisfied. The paired-samples t-test showed a significant improvement following the intervention, t(19) = 8.587, p < 0.001, with a very large effect (Cohen’s dz ≈ 1.92), and the normality assumptions were satisfied. These findings suggest that embedding scanning cues within diamond passing drills is an effective approach to enhance passing performance in youth players by combining technical execution with perceptual–cognitive decision-making demands.